Catalytic cracking of M-100 fuel oil: relationships between origin process parameters and conversion products - Tatyana V. Shakiyeva; Larissa R. Sassykova; Anastassiya A. Khamlenko; Ulzhan N. Dzhatkambayeva; Albina R. Sassykova; Aigul A. Batyrbayeva; Zhanar M. Zhaxibayeva; Akmaral G. Ismailova; Subramanian Sendilvelan (Chimica Techno Acta)
The development of technologies for processing oil residues is relevant and promising for Kazakhstan, since the main oil reserves of hydrocarbons in the country are in heavy oils. This paper describes the study of the influence of technological modes on the yield and hydrocarbon composition of products formed because of cracking of commercial fuel oil and fuel oil M-100 in the presence of air in the reactor. For catalysts preparation, natural Taizhuzgen zeolite and Narynkol clay were used. It was found that the introduction of air into the reaction zone, in which oxygen is the initiator of the cracking process, significantly increases the yield of the middle distillate fractions. In the presence of air, the yield of diene and cyclodiene hydrocarbons significantly increases compared to cracking in an inert atmosphere. According to the data of IR spectral analysis of M-100 grade oil fractions, in addition to normal alkanes, the final sample contains a significant amount of olefinic and aromatic hydrocarbons. On the optimal catalyst, owing to oxidative cracking of fuel oil, the following product compositions (in %) were established: Fuel oil M-100: gas – 0.8, gasoline – 1.1, light gas oil – 85.7, heavy residue – 11.9, loss – 0.5 and total – 100.0%; commodity Fuel oil (M-100): gas – 3.3, gasoline – 8.4, light gas oil – 84.3, heavy residue – 4.0, loss – 0 and total – 100.0%.